1994
DOI: 10.1121/1.410123
|View full text |Cite
|
Sign up to set email alerts
|

Considerations in bond strength evaluation by ultrasonic guided waves

Abstract: Acoustic wave propagation in a three-layer waveguiding configuration is analyzed. Considering an adhesive layer as a waveguide structure, it is shown that the propagation of guided modes is affected by the bonding quality. A comprehensive study demonstrates the possibility of utilizing measurements on guided wave propagation to detect interfacial weakness between an adhesive and adherend.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

1995
1995
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…The QSA boundary conditions ͓Eqs. ͑1a͒ and ͑1d͔͒ have been widely applied to isolated interfaces 1 as well as to interfaces in layered media, 2,3 or between fibers and a matrix 4 . In connection to systems featuring a characteristic length, such as the thickness of a layer, or the radius of a fiber, the legitimate question arises whether the system's structure affects the elastic properties of the imperfect interface.…”
Section: Introductionmentioning
confidence: 99%
“…The QSA boundary conditions ͓Eqs. ͑1a͒ and ͑1d͔͒ have been widely applied to isolated interfaces 1 as well as to interfaces in layered media, 2,3 or between fibers and a matrix 4 . In connection to systems featuring a characteristic length, such as the thickness of a layer, or the radius of a fiber, the legitimate question arises whether the system's structure affects the elastic properties of the imperfect interface.…”
Section: Introductionmentioning
confidence: 99%
“…Over the last two decades, some studies have focused on finding reliable ways of correlating changes in GW propagation with realistic defects in joints. Singher [140,141] investigated the interaction of ultrasonic GW with adhesively bonded single lap metallic joints produced with different surface treatments. Each surface treatment resulted in different bond strength, while the strength should be enhanced for a higher level.…”
Section: New Ultrasonic Welding Application For Polymersmentioning
confidence: 99%
“…Brotherhood et al [5,6] used ultrasonic techniques to detect kissing bonds. Singher et al [7] employed ultrasonic guided waves to evaluate bond quality. It was shown that the quality of the adhesive bond affects the propagation of guided wave modes.…”
Section: Introductionmentioning
confidence: 99%